The Impact of Smoking, Including Hookah, on the Human Body - Elena Emelina (Journal of Global Pharma Technology, 2016)
Smoking is a social problem in society. For smokers, the problem is to quit smoking, for non-smokers-to avoid the influence of smokers and not "catch" their habit, and also-to maintain their health. Tobacco use is the only truly avoidable cause of death worldwide, with approximately half of all long-term smokers dying. World Health Organization (WHO) estimates that there are 1.3 billion people who smoke in the world and forecasts that the number of people who smoke will increase to 1.6 billion by 2025. Currently, 47% of men and 12% of women consume tobacco globally, while only in Europe about 30% of the adult population smokes. In recent decades, the growth of the tobacco epidemic is mainly due to an increase in the proportion of people who smoke in developing countries. At the same time, the smoking epidemic is growing among women and the younger generation. In Russia, the prevalence of smoking is one of the highest in the world. The increase in the prevalence of tobacco smoking in recent years in our country has been facilitated by freer trade in cigarettes, low prices for them and aggressive, widespread, large-scale advertising of tobacco products in all media.Keywords: Tobacco smoking, Hookah smoking, Health, Safety, Smoker.